2014
DOI: 10.1128/aac.02904-14
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Population Pharmacokinetic Model Characterizing the Tissue Distribution of Azithromycin in Healthy Subjects

Abstract: Recent clinical trials indicate that the use of azithromycin is associated with the emergence of macrolide resistance. The objective of our study was to simultaneously characterize free target site concentrations and correlate them with the MIC 90 s of clinically relevant pathogens. Azithromycin (500 mg once daily [QD]) was administered orally to 6 healthy male volunteers for 3 days. The free concentrations in the interstitial space fluid (ISF) of muscle and subcutaneous fat tissue as well as the total concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 50 publications
(56 reference statements)
2
56
1
Order By: Relevance
“…While no data exist on azithromycin levels in rectal mucus, azithromycin has been reported in cervical mucus [11] and gastric mucus [13] so it remains plausible that drug would be present in rectal mucus. Thirdly, high tissue concentrations may not always translate to clinical efficacy due to the relative distribution of azithromycin between different tissue compartments, [39] particularly under the influences of pH [40, 41] and that intracellular concentrations may be potentially unavailable for activity. [41] However despite these pharmacokinetic limitations, observational studies have reported an efficacy of 83% for 1g azithromycin for treating rectal infections [5], supporting the likelihood that reasonable rectal tissue concentrations are being obtained following a 1g dose with the results of this study representing the only published study to date that has quantified rectal concentrations against treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…While no data exist on azithromycin levels in rectal mucus, azithromycin has been reported in cervical mucus [11] and gastric mucus [13] so it remains plausible that drug would be present in rectal mucus. Thirdly, high tissue concentrations may not always translate to clinical efficacy due to the relative distribution of azithromycin between different tissue compartments, [39] particularly under the influences of pH [40, 41] and that intracellular concentrations may be potentially unavailable for activity. [41] However despite these pharmacokinetic limitations, observational studies have reported an efficacy of 83% for 1g azithromycin for treating rectal infections [5], supporting the likelihood that reasonable rectal tissue concentrations are being obtained following a 1g dose with the results of this study representing the only published study to date that has quantified rectal concentrations against treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have focused on the AZM concentration in WBCs, different tissue-specific phagocytes (i.e., the intracellular tissue space), and tissue homogenates (8,(11)(12)(13). The AZM concentration in tissue homogenates represents a mixture of AZM concentrations in the intracellular and extracellular tissue spaces; estimation of drug concentrations in the infection site is not possible.…”
mentioning
confidence: 99%
“…The key pharmacokinetic parameters for antimicrobials commonly used for treatment of STIs are summarized in Table 1. 25,26 Protein binding for azithromycin is particularly interesting as unlike most other antimicrobials, protein binding among healthy individuals is dosedependent, decreasing from 51% at 0.02 µg/mL to 7% at 2 µg/mL, 19 which suggests at high concentrations, protein binding will become saturated resulting in more free drug.…”
Section: Key Pharmacokinetic Parameters Of Antimicrobialsmentioning
confidence: 99%
“…73 One reason for azithromycin's long intracellular half-life is that after it enters the acidic intracellular compartments the drug is trapped within the cell (ion trapping). 26 While ion trapping helps to concentrate the drug intracellular at the site of infection, it does prevent the drug from diffusing back into the plasma. As a result, concerns remain about the presence of low concentrations in extracellular compartments where organisms may replicate, 74 and where prolonged exposures to sub-inhibitory concentrations could induce or select azithromycin resistance.…”
Section: Azithromycinmentioning
confidence: 99%
See 1 more Smart Citation